2015
DOI: 10.1088/0965-0393/23/2/025009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of near-surface Fe precipitates in Cu under high electric fields

Abstract: High electric fields in particle accelerators cause vacuum breakdowns in the accelerating structures. The breakdowns are thought to be initiated by the modification of material surface geometry under high electric fields. These modifications in the shape of surface protrusions enhance the electric field locally due to the increased surface curvature. Using molecular dynamics, we simulate the behaviour of Cu containing a near-surface Fe precipitate under a high electric field. We find that the presence of a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Because of the high stress required to create dislocations in a perfect crystal, various imperfections have been introduced into the simulations. Simulations of subsurface voids [1] and precipitates [13] have shown that these sites can generate plateaus or protrusions on the surface when sufficient external stress is applied.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high stress required to create dislocations in a perfect crystal, various imperfections have been introduced into the simulations. Simulations of subsurface voids [1] and precipitates [13] have shown that these sites can generate plateaus or protrusions on the surface when sufficient external stress is applied.…”
Section: Introductionmentioning
confidence: 99%
“…There are many indications in the literature that metal surfaces behave differently under the influence of a high electric field [2,5,[23][24][25][26][27][28][29][30]. For example, the surface diffusion of adatoms has been found both computationally [31][32][33] and experimentally [34][35][36] to vary depending on the magnitude of the applied field and even become biased when a non-uniform field is present [25,37].…”
Section: Introductionmentioning
confidence: 99%
“…The triggering mechanism of vacuum breakdowns is not entirely clear yet, but experiments have shown a significant field enhancement near copper surfaces, that could lead to breakdown events via positive feedback effect [5]. Such an enhancement could be caused, for instance, by Cu nanotips with aspect ratio of 30-140 [5] whose formation mechanisms have been studied in [6]- [10]. However, such tips have not yet been directly observed on Cu surfaces [5], although there is a report about the formation of field emitters with aspect ratio 3.5-15 on Nb surfaces [11].…”
Section: Introductionmentioning
confidence: 99%